THE ROLE OF THE FLIPPED CLASSROOM IN ENHANCING STUDENTS LEARNING INDEPENDENCE - Selvia Putri Handayani Selvia (Teaching and General Education Studies, 2026)
The advancement of educational technology has led to the development of innovative learning models, one of which is the Flipped Classroom, which has the potential to enhance students’ learning autonomy. This study is a literature review aimed at analyzing the concept of flipped classroom, student learning autonomy, and the role of flipped classroom in promoting autonomous learning based on previous research. The method used was a systematic review of relevant national and international articles and journals discussing the implementation of flipped classroom in educational contexts. The findings indicate that the flipped classroom allows students to study materials independently before class, utilize classroom time for interactive activities, and improve responsibility, engagement, and self-regulation in learning. The review confirms that the implementation of the flipped classroom can enhance students’ learning autonomy, provided it is supported by students’ readiness, teacher competence, and adequate technological facilities. Therefore, the flipped classroom can be considered an effective learning strategy to support 21st-century education.